The Effect of Birth Control on Women's Career Paths and Wages - Lewis, Stephanie (Colloquium: The Political Science Journal of Boston College, 2017)
Throughout the last 50 years, women have experienced increased human capital attainment and earnings. In addition to these increases, birth control utilization has also risen. The purpose of this issue brief is to explore the impact of the birth control pill on women’s career paths and wages. To do so, I analyze existing literature to illustrate the direct effects of early legal access to the pill and its relationship to human capital attainment and future career choices. After evaluating the literature, I examine trends in women’s wages and birth control pill utilization from 1962-2002, utilizing data from the U.S. Census Bureau and the Centers for Disease Control and Prevention. The results indicate that birth control has contributed to an increase in human capital attainment and wages, due to the notion that delayed contraception provides certainty that lowers the cost of long-term career investment decisions. Thus, it is imperative that we consider the vast social and political implications of these results as the U.S. continues to evolve.